CHALLENGES ESP TEACHING IN MIXED-ABILITY CLASSES - Kurbaniyazova, S. (SCIENCE and SOCIETY, 2023)
This article deals with the challenges teachers regularly face when teaching ESP to mixed-ability students. We know that students are different from one another which affects how they learn and need to be taught. Since students come from varying backgrounds, with differing levels of readiness and interest, the traditional method of instruction may not make effective teaching feasible. The paper analyzes researchers’ investigations on problems of mixed-ability classes. The aim of this investigation is to create a positive working environment, which is all part of ensuring better learning.